2020
DOI: 10.1017/s0007485319000920
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent development, survival and reproduction ofApanteles hemara(Nixon) (Hymenoptera: Braconidae) onSpoladea recurvalis(F.) (Lepidoptera: Crambidae)

Abstract: The temperature-dependent development of Apanteles hemara (Nixon), a larval endoparasitoid of the devastating amaranth pest Spoladea recurvalis (F.) was studied in the laboratory at six constant temperatures (10, 15, 20, 25, 30 and 35 °C), a photoperiod of 12L:12D and a relative humidity of 60–70%. Developmental time decreased significantly with increasing temperature within the range of 15–30 °C. The parasitoid's pupal mortality, successful parasitism rate, adult emergence rate and longevity, sex ratio and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…Our findings indicated that the G . bimaculatus female fecundity increased as body size increased, which is consistent with other insect species [ 48 ]. Previous studies have demonstrated that there is always a log-linear correlation between the size of the body and the number of eggs oviposited by cricket during the egg-laying timespan [ 52 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings indicated that the G . bimaculatus female fecundity increased as body size increased, which is consistent with other insect species [ 48 ]. Previous studies have demonstrated that there is always a log-linear correlation between the size of the body and the number of eggs oviposited by cricket during the egg-laying timespan [ 52 ].…”
Section: Discussionsupporting
confidence: 88%
“…icipe by 185.73 days and 190.29 days, respectively. The low-temperature thresholds in the linear equation agree with that of other insect species [ 21 , 48 ]. At the optimum temperature thresholds, G .…”
Section: Discussionsupporting
confidence: 64%
“…Abiotic factors can also affect the development of natural enemies of Lepidopterans. For example, the pupal survival, parasitism rates, longevity and fecundity of the parasitoid, Apanteles hemara (Nixon) (Hymenoptera: Braconidae) significantly decrease with increasing temperature (Agbodzavu, Osiemo‐Lagat, Gikungu, Ekesi, & Fiaboe, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dunn's test was used to compare treatments when the differences were statistically significant (p < 0.05) [9]. The survival of FAWs at egg, larval, and pupal stages was compared among temperatures using a proportion test [32]. Furthermore, survival curves were plotted for each temperature and compared using the nonparametric Kaplan-Meier method [33].…”
Section: Effect Of Temperature On the Fitness Of S Frugiperdamentioning
confidence: 99%